Changing of ATP and Its Metabolites in Blood Samples for Post Mortem Interval: In Vitro Study - Warangkool Chanpan; Churdsak Jaikang; Chaturong Kanchai (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Postmortem interval (PMI) is an important in forensic practice. Many studies in blood and tissue ofanimals have revealed correlation between adenosine triphosphate (ATP) level and PMI. In this study aimed toexplore the correlation between human blood ATP and its metabolites level and PMI in vitro model.Methods: Ten milliliter of venous blood samples were collected form four healthy men and contained in EDTAtube. One milliliter of the blood sample was divided at 0, 1, 2, 4, 8, 12 and 24 h, respectively. The blood sampleswere extracted and measured ATP, adenosine diphosphate (ADP) and adenosine monophosphate (AMP) level byHigh performance liquid chromatography- diode array. Energy charge value was calculated to predict charge ofATP metabolites.Results: The blood ATP, ADP and AMP levels increased in the first hour. The blood ATP, ADP and AMP levelsdid not obviously change before 12 hour. The blood ATP level trended to decrease but the blood ADP and AMPlevels trended to increase after 24 hour. Energy Charge was not change in first 12 hour but trended to decreaseafter 24 hour.Conclusion: The blood ATP level and its metabolites changed after 12 hour and apply for the PMI investigation.